Aspek Yuridis Peralihan Hak Atas Tanah Melalui Proses Hibah - Filbert Cristo Wattilete; Barzah Latupono; Novita Uktolseya (Faculty of Law Pattimura University, 2022)
Introduction: Soil is something that is inseparable from the earth which is called the earth's crust. The transfer of land rights due to a grant must be registered at the land office, assisted by the Land Deed Making Officer. Purposes of the Research: This paper aims to determine the transfer of land rights with the grant process and to determine the factors inhibiting the process of transferring land rights through grants.Methods of the Research: The method used in this paper is normative juridical using a statutory approach, and a conceptual approach.Results of the Research: The results obtained from the results of this study are the granting of a grant to an adopted child by parents to their adopted child as a form of gratitude and affection from parents to their child.